Web text reading: What satisfy both dyslexic and normal learners? - Chen, Chwen Jen; Keong, M.W.; Teh, Chee Siong; Chuah, Kee-Man (IEEE, 2003)
The study employs an exploratory approach to examine the satisfaction of normal and dyslexic learners toward different web text modes. As an average of 10 % of the population shows some traits of dyslexia, presenting web text solely based on the guidelines for normal web users will put users with dyslexia at disadvantage. Due to the ubiquitous use of the web for online learning purposes and the availability of tremendous amount of text on the web, this investigation intends to derive appropriate guidelines for presenting web text that could accommodate both groups of learners. This qualitative study uses a multiple case study design and data are mainly collected via observations and guided interviews. The study reveals that existing dyslexia-friendly text guidelines are also appropriate for normal learners and the use of screen reader, an assistive technology that reads text aloud, does not fit every dyslexic and normal learner.